(3bW eMXhXs ((3GdbGgQIs (3hKjbIs, 2006)
(3GdSfOHGO dbH jQJHW OGFeG HGdHMGQ GdTLGY hgh aj GdbUI eZGeQ LShQ jYed Pgfg jSGYO GdabjQ jYGhf GdeScjf OGQJ Hjfg hHjf LGSQ GdTQjQ eYQcI TQSIs
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdbWIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs